(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and pathological characteristics, as well as treatment-related adverse events, in premenopausal women with stage I–III breast cancer receiving adjuvant endocrine therapy at Ha Tinh General Hospital. Subjects and Methods: A retrospective and prospective longitudinal descriptive study was conducted in 40 patients with stage I–III hormone receptor-positive breast cancer who received adjuvant endocrine therapy with Goserelin combined with tamoxifen or aromatase inhibitors (AIs) between January 2020 and September 2025. Results: The mean age of the patients was 39.48 ± 5.94 years. Tumors measuring >2–5 cm accounted for the largest proportion (55%). The upper outer quadrant was the most common tumor location (42.5%). Invasive carcinoma of no special type (NST) was the predominant histological subtype (90%), and histological grade 2 was the most frequently observed (72.5%). The most common treatment-related adverse events were hot flashes (77.5%), vaginal dryness (65%), arthralgia (50%), and night sweats (45%). Conclusion: Ovarian function suppression with Goserelin combined with tamoxifen or aromatase inhibitors (AIs) was generally well tolerated. No serious treatment-related adverse events were observed.